Effect of paper-factory sludge on yield and nutrient uptake of rice (Oryza sativa) - KARMAKAR, S; MITTRA, B N; GHOSH, B C (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted in acid lateritic soil during the wet season (June to October) of 1995 and 1996 at Kharagpur to study the effect of solid paper-factory sludge and fly ash on transplanted rice (Oryza sativa L.) and find out their suitable time of application. The application of paper-factory sludge with fly ash and chemical fertilizers significantly enhanced grain and straw yields 3.6 and 3.3% than those grown with farmyard manure or its combination with fly ash and chemical fertilizers. The paper-factory sludge along with fly ash incorporated at transplanting proved more effective in increasing yield (7.9%) of rice than their application at 30 days before transplanting. The uptake of N and P was higher (9.5 and 3.3 kg/ha) when paper-factory sludge along with fly ash was applied at transplanting compared with their application at 30 days before transplanting. Such trend in K uptake could be noted only in the second year. The paper-factory sludge and fly ash also improved the soil health by raising pH from 5.30 to 5.82 and organic carbon content from 0.32 to 0.46 %. The availability of N, P and K was also increased from 163.2.to 215..1, 14.9 to 25.3 and 130.0 to 146.8 kg/ha respectively.